2020
DOI: 10.1111/nph.16640
|View full text |Cite
|
Sign up to set email alerts
|

Crassulacean acid metabolism guard cell anion channel activity follows transcript abundance and is suppressed by apoplastic malate

Abstract: Summary Plants utilising crassulacean acid metabolism (CAM) concentrate CO2 around RuBisCO while reducing transpirational water loss associated with photosynthesis. Unlike stomata of C3 and C4 species, CAM stomata open at night for the mesophyll to fix CO2 into malate (Mal) and store it in the vacuole. CAM plants decarboxylate Mal in the light, generating high CO2 concentrations within the leaf behind closed stomata for refixation by RuBisCO. CO2 may contribute to stomatal closure but additional mechanisms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Thus, as surmised for stomatal behaviour at night, C i is not the only factor influencing the daytime behaviour of CAM stomata ( von Caemmerer and Griffiths, 2009 ). It is noteworthy in this context that Lefoulon et al (2020) reported that guard cell anion channel activity in K. fedtschenkoi CAM leaves assayed in the light period tracked the temporal pattern of transcript abundance cycling of the genes encoding the channel proteins. Thus, the data presented here, taken together with those reported previously by von Caemmerer and Griffiths (2009) and Lefoulon et al (2020) , are consistent with the proposal that the circadian clock regulates the transcript oscillations of guard cell anion channel genes and through this mediates stomatal closure in the light period in Kalanchoë leaves regardless of metabolic or genetic interventions that reduce nocturnal CO 2 fixation and vacuolar malate accumulation during the preceding dark period.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, as surmised for stomatal behaviour at night, C i is not the only factor influencing the daytime behaviour of CAM stomata ( von Caemmerer and Griffiths, 2009 ). It is noteworthy in this context that Lefoulon et al (2020) reported that guard cell anion channel activity in K. fedtschenkoi CAM leaves assayed in the light period tracked the temporal pattern of transcript abundance cycling of the genes encoding the channel proteins. Thus, the data presented here, taken together with those reported previously by von Caemmerer and Griffiths (2009) and Lefoulon et al (2020) , are consistent with the proposal that the circadian clock regulates the transcript oscillations of guard cell anion channel genes and through this mediates stomatal closure in the light period in Kalanchoë leaves regardless of metabolic or genetic interventions that reduce nocturnal CO 2 fixation and vacuolar malate accumulation during the preceding dark period.…”
Section: Discussionmentioning
confidence: 90%
“…Incorporating this knowledge within a mechanistic mathematical framework will help refine efforts in modeling and guide our understanding of stomata in the real world. There remains much still to do, too, to define the inputs of light and hormones [78,97], soil water potential, and the hydraulic controls imposed, for example, by aquaporins in the root [98,99] as well as developmental and circadian controls such as those of transcription and translation in CAM stomata [100,101], just to name a few of the challenges for the future (see also Outstanding questions).…”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%
“…This is obvious in the case of photosynthetic light harvesting, which ceases during the night, and its rhythms involve metabolic, transcriptional, cellular, and system-level mechanisms. As Lefoulon et al (2020) have recently shown for plants that have CAM (Crassulacean acid metabolism), the nocturnal cessation of anion channel activity in guard cells is due to a stoppage of channel protein synthesis-a physical rather than a mental (sleeping) explanation. In no way does the ubiquitous presence of the day-night cycle in organisms imply the presence of consciousness.…”
Section: Anesthetics Consciousness and Sleepmentioning
confidence: 99%